2015
DOI: 10.4028/www.scientific.net/amr.1123.338
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sokka Clay on the Tensile and Burning Properties of rPP/Clay Composite

Abstract: Materials engineering, in order to achieve weight reduction and cost saving, was widely developed using plastic-based composite materials, like polypropylene (PP). As the large consumption of PP, the recycled polypropylene (rPP) was potential for producing rPP-based composites for car body panels. However, it had to have high mechanical and burning properties, and it can be achieved using clay particle as filler, like local clay from Sokka Kebumen Indonesia. The clay particle was made from rejected Sokka tile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The fiber was cut to the size of the molding, and then the resin–filler mixture was poured into the molding according to the number of layers made. After 24 h, the composite was removed from the molding and then post-cured in an oven at 100 °C for 60 min [ 41 ]. The composites were cut to produce the test samples according to ASTM standards, i.e., ASTM D 635 for burning testing, ASTM D 790 for flexural testing and ASTM D 5941 for Izod impact testing [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fiber was cut to the size of the molding, and then the resin–filler mixture was poured into the molding according to the number of layers made. After 24 h, the composite was removed from the molding and then post-cured in an oven at 100 °C for 60 min [ 41 ]. The composites were cut to produce the test samples according to ASTM standards, i.e., ASTM D 635 for burning testing, ASTM D 790 for flexural testing and ASTM D 5941 for Izod impact testing [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, many researchers synthesized pumice [ 29 , 30 , 35 ] and combined it with other flame retardants, such as phosphorus-based flame retardant, ammonium polyphosphate, zinc hydroxystannate, magnesium hydrate, ATH, nanosilica, nanoalumina and nanoclay [ 41 ]. However, at present, there are still few, and no one has even discussed the combination of four flame retardants at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…The pristine MMT is known as a material that is easy to agglomerate and hard to intercalate inside the matrix [50] [51]. Furthermore, this result indicates that the ATH and pristine MMT particles fail to make adequate surface interaction [52]. With regards to flexural modulus, it is found that the samples with MMT tend to be less rigid than the GFRP with ATH only (CA60) but almost the same value as the neat GFRP.…”
Section: Mechanical Properties Of Gfrp Filled With Ath and Mmtmentioning
confidence: 97%
“…In a study of fibre-reinforced polymer composites, an increase in voids can lead to a decrease in flexural strength [53]. The voids are the result of low interfacial bonding between filler and matrix [52]. The lowest percentage of void content was obtained by base sample C at 0.9 %, while the highest was found in sample CM60 by 23.9%.…”
Section: Mechanical Properties Of Gfrp Filled With Ath and Mmtmentioning
confidence: 98%
“…Other studies have revealed that reinforcing fibers might affect the properties of GFRP composites [ 12 , 13 , 14 , 15 ]. The addition of reinforcing materials such as glass or carbon fiber can increase the strength and modulus of rPP/clay composite, thereby making possible its application as a structural component in vehicle bodies [ 16 ]. Abburi Lakshman Kumar et al [ 17 ] observed that the direction of fiber reinforcement impacted the mechanical properties and machinability of GFRP composites.…”
Section: Introductionmentioning
confidence: 99%